e-VLBI observations of GHz-peaked spectrum radio sources in nearby galaxies from the AT20G survey - Hancock, P.; Tingay, Steven; Sadler, E.; Phillips, C.; Deller, A. (Wiley-Blackwell Publishing Ltd., 2009)
Gigahertz-peaked spectrum (GPS) radio sources are thought to be young objects which later evolve into Fanaro-Riley type I (FR I) and FR II radio galaxies. We have used the Australia Telescope 20 GHz (AT20G) survey catalogue to select a uniform sample of GPS sources with spectral peaks above 5 GHz, which should represent the youngest members of this class. In this paper, we present e-VLBI observations of 10 such objects which are associated with nearby(z< 0.15) galaxies and so represent a new population of local, low-power GPS sources. Oure-VLBI observations were carried out at 4.8 GHz with the Australia Telescope Long Baseline Array (LBA) using a real-time software correlator. All 10 sources were detected, and wereunresolved on scales of ~100 mas, implying that they are typically less than 100 pc in linear size